Good Life Now - Corinna Anderson (Footprint)
Cedric Price’s architecture approaches time and space atypically, focusing primarily on the needs and desires of the user. His ‘short-life’ housing system, designed in 1970–1972 in response to a national crisis of housing provision, takes consumer choice as the organising principle of its design. Its formal flexibility blurs the separation between the house and workplace, while its customisability and disposability reduces the family home to an expendable commodity. The short-life house accommodates a lifestyle of precarity characteristic of neoliberal society, aligning with neoliberal discourses on society emergent in Britain at the beginning of the 1970s.